The association between sleep parameters and sarcopenia in Japanese community-dwelling older adults. (June 2023) - Shibuki, Takuma; Iida, Miho; Harada, Sei; Kato, Suzuka; Kuwabara, Kazuyo; Hirata, Aya; Sata, Mizuki; Matsumoto, Minako; Osawa, Yusuke; Okamura, Tomonori; Sugiyama, Daisuke; Takebayashi, Toru
Highlights: We examined the association between sleep duration and sarcopenia and its components such as low muscle mass (LMM), low muscle strength (LMS), and low physical performance (LPP). Long sleep had a positive association with sarcopenia, and LMS and LPP indicated strong positive association with long sleep. When the data were stratified by sex, functional aging (such as a decline in measured physical performance) was found to be associated with long sleep in both sexes. In long sleepers, there were no associations between insomnia and sarcopenia and its components. Long sleep and poor sleep quality did not appear to synergize to further increase the risk of sarcopenia, although prolonged sleep and insomnia affected muscles. Abstract: Purpose: This study aimed to examine the association between sleep duration and quality and sarcopenia, assessed by factors such as low muscle mass (LMM), low muscle strength (LMS), and low physical performance (LPP) among older community-dwellers in Japan. Methods: In this cross-sectional study, a total of 2, 069 (men, 902; women, 1, 167) participants aged 65 to 80 years were included. Sarcopenia and each low physical function were defined using the definitions of the Asian Working Groups of Sarcopenia 2019. Sleep duration was stratified into three categories: short sleep (<6 h), normal sleep (6-8 h), and long sleep (>8 h). Sleep quality was classified into two groups based on 8-item Athens Insomnia Scale score: insomnia (≥6), and non-insomnia (<6). We analyzed the association between sleep parameters and sarcopenia, including low physical functions, by logistic regression analysis. Results: Compared to normal sleepers, long sleepers had a positive association with sarcopenia (odds ratio [OR] 2.11, 95% confidence interval [CI] 1.25-3.58). In particular, long sleep was strongly associated with LMS (OR 1.77, 95%CI 1.07-2.94) and LPP (OR 1.90, 95%CI 1.25-2.88). On the other hand, poor sleep quality was not associated with sarcopenia in long sleepers, but in normal sleepers. Conclusions: Long sleep was associated with sarcopenia, including LMS and LPP. However, in long sleepers, insomnia was not associated with sarcopenia or any of its components.